Religious Elements in Advertising - on the Margin of a Certain Projekt - Nagórko, Alicja (Vilnius University Open Series, 2021)
This paper refers to the team research led by the author, financed by the German Research Foundation, conducted at the Institute of Slavic Studies at the Humboldt University. In the years 2009–2015 an online dictionary was created under the title Religiöse Lexik in der Allgemeinsprache (Deutsch, Polnisch, Slowakisch, Tschechisch), available online under www2.hu-berlin.de/sacrumprofanum. It is an intensive type dictionary, its purpose is to provide a deep description and not the big number of output token. In a typical lexicographic system based on a grid of dictionary entries taken from the four languages compared here, there is also a column “cultural contexts”, which includes examples of the use of religious words in advertising.